Proposition and analysis of economic feasibility of scenarios for the management of construction waste through inter-municipal consortia - Gonçalves, Gustavo Henrique Vital; de Castro, Marcus Cesar Avezum Alves [UNESP]; de Castro, Marco Aurélio Soares; Schalch, Valdir; Leite, Wellington Cyro de Almeida; da Rocha, Leonardo Brian Gonçalves; Marques Neto, José da Costa (FapUNIFESP (SciELO), 2023)
Construction waste (CW) is currently one of the biggest problems in urban areas, and the proper management of this material is a challenge for most Brazilian municipalities. In this context, intermunicipal consortia emerge as an alternative for project feasibility, based on the principle that the search for partnerships can be a more attractive and economical option. Thus, this work aimed to evaluate the economic viability of three different scenarios for the implementation of CW management and recycling infrastructures for the formation of an intermunicipal consortium in the municipalities belonging to the Baixo Pardo/Grande Watershed (UGRHI 12). Through visits and interviews with public managers, it was found that none of the municipalities of UGRHI 12 has adequate infrastructure for the management of generated construction waste. Economic feasibility analyses showed that sharing a CW recycling plant, a transshipment and sorting area, and a landfill, without showing the most advantageous scenario, resulting in an TIR of 78.79% and a VPL of R$ 29,094,983.16, and a payback of 1 year and 7 months. However, in the three scenarios analyzed, it was found that the shared management of construction waste can be viable and profitable, and can bring cost reduction and scale gain.
Proposição e análise de viabilidade econômica de cenários para o gerenciamento de resíduos da construção civil por meio de consórcios intermunicipais
Keywords: construction waste; economic viability; intermunicipal consortia